(untitled) (The Review of Diabetic Studies, 2025)
Employee Engagement is an important aspect in the Banking sector because it is directly related with Employee performance. As service oriented sector the banks want to focus on employees involvement in the job and their performance. This can be achieved by the banks by properly investing in the Human Resource Development Practices. The researcher made the study in North Malabar Region of Kerala by comparing both Private sector and Public Sector Banks and selected 262 employees from both public and private sector banks as samples using convenient random sampling techniques. The researcher collected data through questionnaire. To analyze the data, the researcher employed statistical tools like Factor analysis and regression analysis. The result shows a positive and significant relationship exist between the Human resource Development practices and Employee engagement practices in both Public sector and Private sector banks